Calculus early transcendental functions : multivariable - Smith, Robert T. (Robert Thomas) 1955- (McGraw-Hill Higher Education, 2007)
Combines the elements of reform, with the reliable aspects of mainstream calculus teaching. This book provides applications that aim to, appeal to students' interests and demonstrate the elegance of math in the world around us. It includes: an organization placing all transcendental functions, an introduction to L'Hopital's Rule, and others.